ANALISIS FRAMING PEMBERITAAN KASUS KEKERASAN SEKSUAL PADA ANAK DI MEDIA ONLINE TRIBUN-MEDAN.COM DAN KOMPAS.TV - Aisyah, Siti; Harahap, Nursapia (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
During this time, the Internet has had a huge impact on people's lives. The rapid development of technology has made it very easy for people to access everything in the world. Thanks to the Internet and mass media, parents and young people alike have access to information quickly and easily. The purpose of this study is to examine how online media formulate the messages they write. This study uses a qualitative descriptive approach. This research targeted two web-based media, namely Tribun-Medan.Com and Kompas.Tv, and the research topic was sexual violence against children under 12 in Medan city. Research has shown differences and similarities, especially in the structure of the scripts, i.e. the 5W + 1H elements. In addition, there are differences in title choice between the two media, such as the use of different words and languages.